Infection of maize leaves with Ustilago maydis prevents establishment of C4 photosynthesis. - Engelsdorf, Timo; Sonnewald, Uwe; Horst, Robin; Voll, Lars (Journal of Plant Physiology, 2008)
The Basidiomycete fungus Ustilago maydis is the common agent of corn smut and is capable of inducing gall growth on infected tissue of the C4 plant maize (Zea mays). While U. maydis is very well characterized on the genetic level, the physiological changes in the host plant in response to U. maydis infection have not been studied in detail, yet. Therefore, we examined the influence of U. maydis infection on photosynthetic performance and carbon metabolism in maize leaf galls. At all stages of development, U. maydis-induced leaf galls exhibited carbon dioxide response curves, CO2 compensation points and enzymatic activities that are characteristic of C3 photosynthesis, demonstrating that the establishment of C4 metabolism is prevented in infected tissue. Hexose contents and hexose/sucrose ratio of leaf galls remained high at 6 days post infection, while a shift in free sugar metabolism was observed in the uninfected controls at that time point. Concomitantly, transitory starch production and sucrose accumulation during the light period remained low in leaf galls. Given that U. maydis is infectious on young developing tissue, the observed changes in carbohydrate metabolism suggest that the pathogen manipulates the developing leaf tissue to arrest sink-to-source transition in favor of maintaining sink metabolism in the host cells. Furthermore, evidence is presented that carbohydrate supply during the biotrophic phase of the pathogen is assured by a fungal invertase.
Keywords: C-4 photosynthesis; corn smut; invertase; maize; Ustilago maydis